APPLICATION OF VIRTUAL REALITY TECHNOLOGY IN LANGUAGE LEARNING (Eureka Journal of Education & Learning Technologies, 2026)
The fast development of digital technologies has fundamentally altered the face of modern education. Of these innovations, Virtual Reality (VR) has emerged as a crucial tool for improving the language learning experience. Virtual Reality allows students to practice their language skills in realistic settings without having to leave the classroom, thanks to immersive and interactive environments. This article addresses the role of Virtual Reality technology in language acquisition, as well as their benefits, drawbacks, and pedagogical implications. According to the study, virtual reality can improve learners' speaking abilities, motivation, engagement, and cultural awareness. Furthermore, virtual reality training allows for authentic communication and contextualized learning, making language acquisition more meaningful and successful. The research concludes by suggesting that the use of Virtual Reality in language education can help develop communicative skills and stimulate novel teaching strategies in higher education.
Keywords: Virtual reality, language learning, educational technology, communicative competence, digital education, immersive learning, higher education, and English language teaching.